The Absence of a Very Long Chain Fatty Acid (VLCFA) in Lipid A Impairs Agrobacterium fabrum Plant Infection and Biofilm Formation and Increases Susceptibility to Environmental Stressors - Iwona Komaniecka; Kamil Żebracki; Andrzej Mazur; Katarzyna Suśniak; Anna Sroka-Bartnicka; Anita Swatek; Adam Choma (Molecules)
The Agrobacterium fabrum C58 is a phytopathogen able to infect numerous species of cultivated and ornamental plants. During infection, bacteria genetically transform plant cells and induce the formation of tumours at the site of invasion. Bacterial cell wall components play a crucial role in the infection process. Lipopolysaccharide is the main component of Gram-negative bacteria’s outer leaflet of outer membrane. Its lipophilic part, called lipid A, is built of di-glucosamine backbone substituted with a specific set of 3-hydroxyl fatty acids. A. fabrum incorporates a very long chain hydroxylated fatty acid (VLCFA), namely 27-hydroxyoctacosanoic acid (28:0-(27OH)), into its lipid A. A. fabrum C58 mutants deprived of this component due to mutation in the VLCFA’s genomic region, have been characterised. High-resolution mass spectrometry was used to establish acylation patterns in the mutant’s lipid A preparations. The physiological properties of mutants, as well as their motility, ability to biofilm formation and plant infectivity, were tested. The results obtained showed that the investigated mutants were more sensitive to environmental stress conditions, formed a weakened biofilm, exhibited impaired swimming motility and were less effective in infecting tomato seedlings compared to the wild strain.